2010
DOI: 10.1016/j.ecosys.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Default rates in the loan market for SMEs: Evidence from Slovakia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
18
0
2
Order By: Relevance
“…It then stagnated during the financial crisis, avoiding a strong deleveraging episode. Overall, credit development in Slovakia was not characterised by the accumulation of financial vulnerabilities to the same extent as in other emerging economies in Central and Eastern Europe (Fidrmuc and Hainz, 2010). Slovakia achieved a substantial reduction in gross public debt during the preparations for the euro adoption ( Figure 12B).…”
Section: Interactions Between Euro Adoption and The Crisis Went In Bomentioning
confidence: 91%
“…It then stagnated during the financial crisis, avoiding a strong deleveraging episode. Overall, credit development in Slovakia was not characterised by the accumulation of financial vulnerabilities to the same extent as in other emerging economies in Central and Eastern Europe (Fidrmuc and Hainz, 2010). Slovakia achieved a substantial reduction in gross public debt during the preparations for the euro adoption ( Figure 12B).…”
Section: Interactions Between Euro Adoption and The Crisis Went In Bomentioning
confidence: 91%
“…Bonfim (2009) uses the Banco de Portugal Central Credit Register data, and a firm is considered defaulted if it has credit overdue; Carling et al (2007) use credit data from a major Swedish bank: customers are considered defaulted if principal or interest payments are 60 days overdue, and a bank official has to make a judgement and reach the conclusion that any such payment is unlikely to occur in the future. Behr and Güttler (2007) estimate the probability of default for German SMEs, using data from a major German bank engaged in financing small and medium enterprises, while Fidrmuc and Hainz (2010) analyze the data from a Slovakian commercial bank. Finally, McCann and McIndoe-Calder (2012) study Irish SMEs' probability of default using Credit Register data: a firm is considered defaulted if it has loans 90 days past due.…”
Section: Related Literaturementioning
confidence: 99%
“…Evidence of skewness toward the high end of the distribution was also reported. Fidrmuc et al (2006) used a unique unbalanced panel of nearly 700 short-term loans made to SMEs in Slovakia between January 2000 and June 2005. They concluded that liquidity and profitability factors are important determinants of SMEs defaults, while debt factors are less robust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there is evidence on the default and mortality rates of bonds, it is hard to transfer the results in this field to corporate loans (Wongnaa and Awonyu-Vitor, 2013). The limit studies on default of bank loans are such on syndicated loans to corporate debtors (Altman and Suggitt, 2000, Yong Seo, 2011and Sylvester, 2013 and pattern of loans to individual firms in a fast growing emerging economy (Fidrmuc et al, 2006 andSaunders &Allen, 2002). What is still missing is evidence of the default model of loans to SMEs in a developing economy.…”
Section: Introductionmentioning
confidence: 99%